Cooperativity, cage effect and hopping diffusion in supercooled liquids and glasses - Bakai, A.S.; Lazarev, N.P. (Condensed Matter Physics, 2003)
Molecular dynamic simulations of structure, thermodynamic and kinetic
properties of model metallic Ag–Cu alloy are performed to elucidate its
behavior at glass transition. In spite of small variations of inherent structure
of the alloy the relaxation kinetics undergo dramatic changes at the
glass transition. The time dependences of the mean square displacements
and the non-Gaussianity parameter show the signs of anomalous diffusion
in an intermediate time region. The analysis of time evolution of van Hove
correlation function indicates the existence of both jump displacements and
short-range cooperative atomic rearrangements. Below Tg these cooperative
rearrangements do not contribute to a long-range diffusion but they
still dominate the relaxation at short time. Методом молекулярної динаміки виконано моделювання структури
та термодинамічних і кінетичних властивостей металевого сплаву
Ag–Cu з метою з’ясування його поведінки при переході рідина-скло.
Незважаючи на незначні зміни структури потенціального рельєфу,
релаксаційна кінетика зазнає драматичних змін при цьому переході. Залежність від часу середньоквадратичних віддалень атомів та
параметру негаусовості виявляють ознаки аномальної дифузії в області проміжного часового масштабу. Аналіз еволюції в часі кореляційної функції Ван Гова виявляє наявність як стрибкових, так і кооперативних переміщень атомів. При температурах нижче Tg кооперативні переміщення не дають внеску в дифузію на велику відстань,
але вони продовжують домінувати в короткочасних релаксаційних
процесах.